Effects of surgery on survival of patients aged 75 years or older with oral tongue squamous cell carcinomas - Yujiao Li (Nature Portfolio, 2021)
Abstract The objective of this study is to assess prognostic value of surgery for elderly oral tongue squamous cell carcinomas (OTSCC) patients. Patients with OTSCC were extracted from the SEER database between 2010 and 2014. The distributions of categorical demographic and clinicopathological characteristics were determined for different age groups: the 75–79, 80–84, and 85–102 years old groups. Univariate and multivariate analyses were performed to determine the effects of each variable on survival. A total of 1064 patients were analyzed. 75–79 years old patients tended to be male and rate of surgery declined with advancing age (P < 0.001). 75–79 years old patients more frequently presented with advanced stage compared to their older peers (P = 0.002). Compared to surgery groups, the hazard ratios for no surgery groups were 2.856 (95% CI 2.267–3.599; (P < 0.001)) for OS and 3.687 (95% CI 2.561–5.308; (P < 0.001)) for CSS in multivariable analysis. In subgroup analysis, the effect of no surgery was significantly associated with a higher risk of poor CSS in patients aged 75–79 years, 80–84 years and 85–102 years (P < 0.001, respectively). Our results showed that there were a series of factors contributing to poor outcomes in the elderly OTSCC patients, including clinicopathological characteristics and surgical management. Surgical resection is significantly associated with an improved OS and CSS, but further exploration in larger prospective clinical trials and better prognostic and predictive tools for select old patients for surgery are needed.